2015
DOI: 10.1038/nrneurol.2015.218
|View full text |Cite
|
Sign up to set email alerts
|

Solanezumab—prospects for meaningful interventions in AD?

Abstract: A treatment trial of the monoclonal anti-amyloid antibody solanezumab showed slight benefits in people with dementia due to mild Alzheimer disease. Drug effects on several neuropsychological testing outcomes were statistically significant, but the effect sizes were unlikely to manifest as meaningful functional benefits. Here, we discuss the implications and possible molecular underpinnings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…While prior active or passive immunotherapies have been successful in AD mouse models, success in clinical trials has been elusive. 2 …”
mentioning
confidence: 99%
“…While prior active or passive immunotherapies have been successful in AD mouse models, success in clinical trials has been elusive. 2 …”
mentioning
confidence: 99%
“…Multiple passive vaccinations have progressed to Phase III clinical trials, however none have proved effective in treating the cognitive deficits experienced in AD [ 73 ]. Recently Eli Lilly reported on its vaccine Solaneuzumab, which showed no significant effect on cognition in the overall population it examined for its Phase III trial, but did show some benefits for the younger participants in the study upon post hoc analysis of the data [ 77 ]. The results of the Solaneuzumab trial underscore one of the primary explanations for the failures of both Aβ vaccinations and inhibitors of amyloidogenesis: namely, that these interventions are only effective when given to presymptomatic patients.…”
Section: Current Drug Therapies For Alzheimer’s Diseasementioning
confidence: 99%
“…Also, the passive immunotherapy did not do much better than active immunotherapy. Several antibodies targeting Aβ have failed in clinical trials, including bapineuzumab (Pfizer/Johnson & Johnson) [ 13 , 14 ], Crenezumab (Genentech) [ 15 , 16 ], solanezumab (Eli Lilly) [ 16 18 ] and ponezumab (Johnson & Johnson /Pfizer) [ 19 21 ]. In addition, although passive immunotherapy could overcome some problems of active immunotherapy, there were still inevitable side effects such as amyloid-related imaging abnormalities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A phase Ib trial of aducanumab (Biogen) showed a positive correlation between brain Aβ levels and disease exacerbation as measured by Clinical Dementia Rating [ 29 – 31 ]. Even the failed phase III EXPEDITION3 trial of solanezumab (Eli Lilly) still demonstrated better performance in Clinical Dementia Rating Sum of Boxes and beneficial impacts on Mini-Mental State Examination and Activities of Daily Living [ 17 , 18 , 32 , 33 ]. Thus, despite all kinds of problems, immunotherapy may still be the better approach to modify the extent of neurodegeneration in AD currently [ 34 ].…”
Section: Introductionmentioning
confidence: 99%